2022
DOI: 10.1016/j.aej.2022.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of time-fractional SIQR Covid-19 mathematical model with fractal-fractional Mittage-Leffler kernel

Abstract: In this manuscript, we investigate a nonlinear SIQR pandemic model to study the behavior of covid-19 infectious diseases. The susceptible, infected, quarantine and recovered classes with fractal fractional Atangana-Baleanu-Caputo (ABC) derivative is studied. The non-integer order and fractal dimension in the proposed system lie between 0 and 1. The existence and uniqueness of the solution for the considered model are studied using fixed point theory, while Ulam-Hyers stability is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…19 The number of infected individuals can be reduced through mass testing, but the implementation of strict and immediate quarantine leads to reductions of about 90% in the total number of cases. 17 It was observed that the numbers of cases of COVD-19 are much higher than those confirmed by SEMUS-Codó. Until May 11, 2021, the number of confirmed cases was 5,466.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…19 The number of infected individuals can be reduced through mass testing, but the implementation of strict and immediate quarantine leads to reductions of about 90% in the total number of cases. 17 It was observed that the numbers of cases of COVD-19 are much higher than those confirmed by SEMUS-Codó. Until May 11, 2021, the number of confirmed cases was 5,466.…”
Section: Resultsmentioning
confidence: 82%
“…Generally, rapid tests are mostly applied to symptomatic individuals, disregarding the huge potential for asymptomatic infected people, since the numbers of infected and unconfirmed cases grow faster than the number of confirmed cases. 12,17 When we use 40% for healthy population in social distancing, as in figure 1(A), COVID-19 cases peaked with more than 10,000 cases, and when we put 40% for infectious population in isolation, the case numbers reached its peak with approximately 5,000 cases, as we can see in figure 2(C), with a large decrease in cases.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, FFOs have been used in the modelling and analysis of HIV infection [24]. The current pandemic COVID-19 has also been investigated with the help of FFOs [25]. Other dangerous and fatal disease like tumor has been studied under nonsingular fractal fractional operator [26].…”
Section: Introductionmentioning
confidence: 99%